ANALISIS DIAGNOSIS KESEHATAN KEPEMIMPINAN DI LEMBAGA DIKLAT (Jurnal Tata Kelola Pendidikan, 2019)
Leadership in an organization has a major influence on achieving its goals. The mainresearch question of this study was thus whether the leadership in the organization isrunning well. Hence, an instrument is required. That leads to why this author wasinterested in researching it with the title "An Analysis of Leadership Health DiagnosticInstruments in Training Institutes." This study aims to make an instrument of leadershiphealth diagnostic that can be useful to determine the health category of each traininginstitutes being observed. Besides, to overcome any issues in carrying out managementfunctions. The method used in this study was a descriptive method with a quantitativeapproach. The study was conducted in the form of questionnaires, with data being gatheredvia google form. The sample of this study was the head centre, leaders at each division,field, and section as well as 165 employees from three training institutes, namely PPPPTKBMTI, PPPPTK IPA, and PPPPTK TK & PLB. The technique used was a proportionalstratified random sampling technique with calculations using the Taro Yamane or Slovinformula. Hence, the finding suggests that the three institutes are interpreted in the"healthy" category. This indicates that leadership activities and management functionshave been well-conducted. Overall, the average calculation results of the general tendencyare 3.54 or equal to 88.5.
Keywords: Instrument; Health; Leadership